Providing decent living with minimum energy: A global scenario. (November 2020) - Millward-Hopkins, Joel; Steinberger, Julia K.; Rao, Narasimha D.; Oswald, Yannick
Highlights: Providing Decent Living with Minimum Energy: A Global Scenario. As ecological breakdown looms, the basic material needs of billions remain unmet. We estimate the minimal energy for providing decent living globally & universally. Despite population growth, 2050 global energy use could be reduced to 1960 levels. This requires advanced technologies & reductions in demand to sufficiency levels. But 'sufficiency' is far more materially generous than many opponents often assume. Abstract: It is increasingly clear that averting ecological breakdown will require drastic changes to contemporary human society and the global economy embedded within it. On the other hand, the basic material needs of billions of people across the planet remain unmet. Here, we develop a simple, bottom-up model to estimate a practical minimal threshold for the final energy consumption required to provide decent material livings to the entire global population. We find that global final energy consumption in 2050 could be reduced to the levels of the 1960s, despite a population three times larger. However, such a world requires a massive rollout of advanced technologies across all sectors, as well as radical demand-side changes to reduce consumption – regardless of income – to levels of sufficiency. Sufficiency is, however, far more materially generous in our model than what those opposed to strong reductions in consumption often assume.